(untitled) (Journal of actual problems of jurisprudence, 2019)
In a preliminary investigation and trial of cases to any citizen, brought in as a suspect, accused or defendant Constitution of the Republic of Kazakhstan and the Criminal – Procedural Code of the Republic of Kazakhstan shall have the right to be protected from prosecution.Inalienable, natural right to defend arises from the competitive structure of the process, when a strong charge to resist adequate protection.The highest degree of protection of the rights and lawful interests of individuals, the more the person involved in the orbit of the criminal justice is the hallmark of a democratic and legal state. Keywords: competitiveness, equality, equal rights,accusation, protection, justice